PENERAPAN MODEL PENERAPAN MODEL PEMBELAJARAN GUIDED INQUIRY UNTUK MENINGKATKAN HASIL BELAJAR PESERTA DIDIK KELAS XII IPS 2 PADA MATERI PELUANG DI SMA NEGERI 1 SAMPANG TAHUN PELAJARAN 2022/2023: PENERAPAN MODEL - Syaiful Hidayat (Lembaga Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Keguruan dan Ilmu Pendidikan PGRI Sampang, Indonesia, 2024)
This research problem is: What is the learning outcome after being given guided learning on the learning model for the chances material in XII IPS 2 grade students of SMA Negeri 1 Sampang? The general goal of this research is: To increase the learning outcome in XII IPS 2 grade students of SMA Negeri 1 Sampang by using guided learning on the learning model for the chances material. This research is a Classroom Action Research (CAR) of the application of guided inquiry in the learning model and uses three cycles. After doing several steps, this model is expected to have positive impact in the students’ learning outcome. The subject of this research is the students of XII IPS 2 grade in SMA Negeri 1 Sampang of the odd semester in 2022/2023 education year. The total of the students is 30, consists of 19 male students and 11 female students. The basic competences are: KD 3.5 contains describing and determining chances compound incident (chances of free from each other incidents, mutually exclusive, and conditional incident) from a certain random experiment; and KD 4.5 contains finishing problems related to the chances of the compound incidents (chances of free from each other incidents, mutually exclusive, and conditional incident). The collecting data method uses observation and evaluation. Data analysis focuses on the attitude, skill, and knowledge competence. The result of this research shows that there are positive impacts in increasing the students’ learning outcome, those are: study completeness is in 100% in the attitude competence; 100% in the skill competence; and 86% in the knowledge competence